Evaluation of an automated reader for disc diffusion antimicrobial susceptibility testing in a routine microbiology laboratory - Patricia Orlandi Barth; Xander Cortez Pinzas; Vitória Torrescasana Teixeira; Larissa Lutz; Caroline Collioni Constante; Bruno Rodriguez Tondin; André Frotta Müller; Danton Pereira da Silva Junior; Paulo Roberto Stefani Sanches; Afonso Luís Barth (PLoS ONE, 2026)
Antimicrobial susceptibility testing (AST) is essential for determining the in vitro activity of antimicrobial agents against specific microorganisms. Reliable data from AST is needed for the detection of resistance mechanisms which are crucial to ensure appropriate treatment of patients in healthcare settings or in the community. Automated AST readers of the inhibition zone provide valuable tools for standardizing the testing process in microbiology laboratories, enabling faster and more reliable interpretation of results. The aim of this study was to evaluate AntibiHórus, an in-house developed automated disc diffusion AST reader, by comparing its performance against manual reading of the inhibition zones using a ruler. A total of 500 ASTs, including both Gram-negative and Gram-positive bacteria, were evaluated using 22 different antimicrobial discs, resulting in 4,709 inhibition zone measurements. Manual readings with a ruler were compared with the automated readings from AntibiHórus. The overall categorical agreement (CA) between AntibiHórus and manual reading was 96.86%, with minimal error rates, 2.08% for Very Major Errors (VME), 0.30% for Major Errors (ME), and 0.76% for Minor Errors (MiE). Statistical analysis showed a strong correlation between methods (Pearson correlation coefficient R ≥ .95). The findings demonstrate that AntibiHórus is a reliable tool for routine microbiology laboratory work, enhancing the efficiency, standardization, and accuracy of AST analysis by automating inhibition zone measurement and interpretation.